Private equity challenge - Delo financial and strategic analysis - Bitsch, Sebastian (2022)
The “Private Equity Challenge” Field Lab Work Project simulates and outlines a real deal regularly conducted by private equity firms. The objective of this project is to analyze a target company, develop an investment strategy and model a leveraged buyout for the chosen company. This group identified “DELO –Industrial Adhesives GmbH” as an attractive target company. The following analysis provides one par tof the full analysis with special focus on the business plan and valuation.